A novel Citrus sinensis peel ash coated magnetic nanoparticles as an easily recoverable solid catalyst for biodiesel production. (15th February 2021) - Changmai, Bishwajit; Rano, Ruma; Vanlalveni, Chhangte; Rokhum, Lalthazuala
Graphical abstract: Highlights: FAME production from WCO using CSPA@Fe3 O4 solid catalyst is reported. The activation energy of 34.4 KJ mol −1 was noted for the transesterification of WCO. High yield of 98% of FAME was obtained with 6 wt% catalyst within 3 h. CSPA@Fe3 O4 catalyst is very stable due to the core–shell structure. The synthesized can be reused for 9 successive cycles. Abstract: A magnetic nano-sized solid catalyst derived from bio-waste Citrus sinensis peel ash (CSPA)@Fe3 O4 was developed for the synthesis of biodiesel from waste cooking oil (WCO). The core–shell structure of the catalyst enhanced the surface properties and maintained a controlled size and shape of the catalyst, thus improved the catalyst stability to a great extent. The synthesized catalyst was characterized by several analysis techniques. The high amount of potassium and calcium in the Citrus sinensis peel ash (CSPA) catalyst makes it extremely basic and played an important catalytic role in the transesterification of WCO. The CSPA@Fe3 O4 catalyzed transesterification afforded a maximum biodiesel yield of 98% under the optimized reaction conditions such as 6:1 methanol/oil molar ratio, 6 wt% catalyst loading, 65 °C temperature and 3 h time. The activation energy of the reaction was found to be 34. 41 KJ mol −1, which indicated that the transesterification of WCO using the present catalyst is chemically controlled reaction. Beneficially, the magnetic iron oxide core endorsed easily recoverable of the catalyst from the reaction mixtures by using an external magnet. Moreover, the catalyst showed high physical stability and reactivity up to the 9 consecutive cycles, demonstrating it as a promising solid base catalyst for sustainable production of biodiesel.